Tinjauan Kriminologis Terhadap Faktor-Faktor Kasus Percobaan Pembunuhan Menggunakan Minuman Kopi Beracun Di Kota Kupang - Nur Aini Badjideh; Karolus Kopong Medan; Sigit Prabowo Sonbait (Law Faculty, Nusa Cendana University, 2026)
The attempted murder case using poisoned coffee drinks that occurred in Kupang City is a serious problem because the act was carried out secretly and can pose a great risk to the victim's safety. This case shows that there are several factors behind the perpetrator committing the act to the victim. So the author conducted this study with the aim of: (1) knowing and explaining the factors that encourage the occurrence of attempted murder cases using poisoned coffee drinks in Kupang City. (2) To find out and explain efforts to overcome attempted murder cases using poisoned coffee drinks in Kupang City. This study uses an empirical legal research type, data collected through document studies and interviews in the field with several sources, and is carried out based on a factual or real approach and through a statutory regulatory approach. Then analyzed descriptively qualitatively. The results of the study show that there are several factors that encourage the perpetrator to commit the attempted murder, both from internal and external factors, as well as penal and non-penal efforts made to overcome the crimes that occur. This study is expected to contribute to the development of strategies for preventing similar crimes and strengthening the criminal system in handling cases of attempted murder using poisoned coffee drinks.